Impact Analysis of Parking Price Adjustment on the Quality of Service of Airport Parking Lots for Light Vehicles - Cheng Cheng; Peng Qi (Journal of Advanced Transportation)
Pricing is a common measure for parking demand management that has been implemented worldwide. However, the impact of parking price on a parking lot’s quality of service is seldom discussed. This study investigated the impacts of a ladder daily maximum fee charging strategy on the quality of service of the Hongqiao International Airport parking lot based on automatic transaction data before and after the strategy was implemented. An evaluation framework considering managers’ and users’ perspectives was designed. The estimation results show that the new price regulation method largely discouraged long-term parking demand and improved the availability of airport parking facilities, especially during long holidays. As a consequence, throughput and income largely increased in the airport, and there were extra time costs during vehicle departures. The price elasticity of parkers with different parking durations was further estimated. The results showed that price sensitivity is relatively inelastic but varies based on parking duration.